2015
DOI: 10.17269/cjph.106.4938
|View full text |Cite
|
Sign up to set email alerts
|

Self-report Pregnancy Physical Activity Questionnaire overestimates physical activity

Abstract: OBJECTIVES: Physical activity (PA) research during pregnancy relies heavily on indirect/subjective measures of PA, which may be less accurate than directly measured PA. We tested whether the Pregnancy Physical Activity Questionnaire (PPAQ) could accurately estimate PA by comparing PPAQ results to directly measured PA. METHODS:In a sample of 29 women who completed the PPAQ, PA was directly measured in the second trimester of pregnancy using Actical® accelerometers (valid day = 10+ hours; 4-7 valid days). Activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 22 publications
6
27
1
Order By: Relevance
“…In most studies, an accelerometer was used as a comparison measure. Eight studies [ 42 46 , 49 , 51 , 55 ] assessed the measurement properties of the Pregnancy Physical Activity Questionnaire (PPAQ) [ 44 ] or adaptations of this questionnaire (e.g., Japanese version). Another study [ 48 ] evaluated the long form of the IPAQ, whereas two studies (of reliability and construct validity), reported in one article [ 52 ], evaluated the short form of the IPAQ (IPAQ-SF).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies, an accelerometer was used as a comparison measure. Eight studies [ 42 46 , 49 , 51 , 55 ] assessed the measurement properties of the Pregnancy Physical Activity Questionnaire (PPAQ) [ 44 ] or adaptations of this questionnaire (e.g., Japanese version). Another study [ 48 ] evaluated the long form of the IPAQ, whereas two studies (of reliability and construct validity), reported in one article [ 52 ], evaluated the short form of the IPAQ (IPAQ-SF).…”
Section: Resultsmentioning
confidence: 99%
“…The results of studies of the construct validity of (versions of) the PPAQ were predominantly insufficient, such as for the Vietnamese [ 51 ], Japanese [ 49 ], English [ 44 , 46 ], Chinese [ 55 ], and bilingual [ 46 ] versions of the questionnaire. Likewise, the second study [ 42 ] of the English version revealed insufficient construct validity for all scores expect for LT-MVPA. The Turkish version of the PPAQ [ 45 ] showed sufficient validity for the assessment of total PA due to a high correlation with the pedometer but insufficient ratings for all other estimates.…”
Section: Resultsmentioning
confidence: 99%
“…Second, an overestimation of physical activity or misclassification of intensity is possible with self-report. However, data derived from the PPAQ correlate with acceptable accuracy with objective data obtained by accelerometry during pregnancy,19 20 despite a possible overestimation 46. To establish the precise effects of various physical activity intensities and levels on birth weight, future cohorts should nevertheless use objective measures of physical activity such as accelerometry.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the authors used the MPAQ to retrospectively assess self-reported LTPA performed during the nine months of pregnancy plus three months before pregnancy. Since objective measurements of PA delivers more valid results than self-reported (subjective) measurements [54, 55], future studies assessing PA in pregnancy should use objective devices such as accelerometers, or use an exercise intervention (randomized design).…”
Section: Discussionmentioning
confidence: 99%